2020
DOI: 10.3389/fgene.2020.584460
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis of m6A Methylome in Cisplatin-Induced Acute Kidney Injury and Berberine Alleviation in Mouse

Abstract: BackgroundN6-methyladenosine (m6A) is the most abundant modification known in mRNAs. It participates in a variety of physiological and pathological processes, such as metabolism, inflammation, and apoptosis.AimsTo explore the mechanism of m6A in cisplatin-induced acute kidney injury (AKI) and berberine alleviation in mouse.MethodsThis study investigated the N6-methyladenosine (m6A) methylome of kidneys from three mouse groups: C57 mice (controls), those with CI-AKI (injury group, IG), and those pretreated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 65 publications
1
16
0
Order By: Relevance
“…We further revealed that the expression patterns of m 6 A-modified RNAs changed significantly in response to cisplatin. Similar to our results, a recent study also found differences in the expression profile of m 6 A methylation in the kidney tissues after cisplatin treatment (Shen J. et al, 2020). The parent genes of the differentially expressed m 6 A methylated mRNAs, such as Krt20, Ccdc85b, and Serpina3n were found to be upregulated in both studies, while Ctnna2, Afm, Pzp, and Dgkg were downregulated.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We further revealed that the expression patterns of m 6 A-modified RNAs changed significantly in response to cisplatin. Similar to our results, a recent study also found differences in the expression profile of m 6 A methylation in the kidney tissues after cisplatin treatment (Shen J. et al, 2020). The parent genes of the differentially expressed m 6 A methylated mRNAs, such as Krt20, Ccdc85b, and Serpina3n were found to be upregulated in both studies, while Ctnna2, Afm, Pzp, and Dgkg were downregulated.…”
Section: Discussionsupporting
confidence: 91%
“…This study highlights an unappreciated systemic role of renal glucose metabolism in kidney damage (Legouis et al, 2020). In cisplatin-induced AKI, a recent study indicated that genes with differently altered methylation of m 6 A sites were highly enriched in metabolic processes (Shen J. et al, 2020). Regarding amino acid metabolism, the levels of phenylalanine, allantoic acid, methylcysteine, gamma-aminobutyric acid, beta-alanine, and aminoadipic acid in the renal cortex of Sprague Dawley rats were increased significantly after intraperitoneal injection of endotoxin lipopolysaccharide (LPS) (Ping et al, 2019).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In an I/R AKI mouse model, transcriptome sequencing of renal tubules suggested that metabolic maladaptation was implicated in AKI progression to chronic fibrosis, with massive lipid droplet accumulations observed in renal tubular epithelial cells ( Zhang et al, 2018 ). In cisplatin-induced acute kidney injury, methylated RNA immunoprecipitation sequencing and RNA sequencing revealed that metabolic processes and cell death were activated in the injury group ( Shen et al, 2020 ). In mouse sepsis-associated AKI, the differentially expressed genes (DEGs) from three paired tissues’ RNA-seq were enriched in the nod-like receptor signaling, toll-like receptor signaling, and JAK/STAT signaling pathways ( Yang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The general mechanisms of these natural products are summarized in Figure 5 . These include blockage of cisplatin renal uptake and transportation [ 22 ], inhibition of oxidative stress [ 96 , 97 ], inhibition of inflammation [ 98 , 99 ], inhibition of P53 signaling pathways [ 52 ], inhibition of mitogen-activated protein kinases [ 100 ], attenuation of cell death, and enhancement of cellular antioxidant defense systems such as SOD, catalase, and the Nrf2 pathway [ 101 , 102 ]. Autophagy and mitophagy are also involved in cisplatin-induced kidney injury [ 51 , 103 ] and can be modulated by natural products for protective purposes [ 104 , 105 , 106 , 107 ].…”
Section: Counteracting Effects Of Natural Products Derived From Plantsmentioning
confidence: 99%